Family Christmas at Frances Kamp's Home - Watkins, Howard::::::::: (1987)
Christine Kamp, Jerry Kamp, Howard Watkins, Robin Watkins, Frances Kamp and Adam Watkins Opened Christmas presents of Clue, Wheel of Fortune, Alphabet Game and Give Peace a Chance